Herbal Bioenhancers in Veterinary Phytomedicine - Yurdakok-Dikmen, Begum; Turgut, Yagmur; Filazi, Ayhan (Frontiers in Veterinary Science, 2018)
Herbal bioenhancers are active phytomolecules that increase the bioavailability, bioefficacy and biological activity of various drugs when coadministered at low concentrations. These valuable compounds reduce the dose, increase the treatment rate, decrease the treatment duration, drug resistance or related adverse reactions which have economical implications in livestock and pet medicine. Eventhough the concept of herbal bioenhancers are known for years through Ayurvedic medicine, the underlying mechanisms remains unclear. The main mechanisms involved are related to drug absorption (effect on solubility, drug efflux and transport proteins, increased permeability in gastrointestinal system) and drug metabolism (inhibition/induction of drug metabolysing enzymes, thermogenic effect). Due to species specific differences in these mechanisms, corresponding data on human and laboratory animal could not be attributed. As multidrug resistance is a major treat to both human and animal health, within “One Health” concept, efficient therapeutical strategies are encouraged by authorities, where focus on herbal supplements as a vast unexploited field remains to be researched within “Bioenhancement Concept.” This review brings insight to mechanims involved in bioenhancing effect, examples of herbal extracts and phytoactive compounds and their potential in the veterinary medicine including different classes of drugs such as antibiotics, anticancerous, antiviral, and antituberculosis.